2013
DOI: 10.1007/s00441-013-1730-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and regulatory roles of FABP5 and FABP7 in oligodendrocyte lineage cells

Abstract: Fatty-acid-binding proteins (FABPs) are key intracellular molecules involved in the uptake, transportation and storage of fatty acids and in the mediation of signal transduction and gene transcription. However, little is known regarding their expression and function in the oligodendrocyte lineage. We evaluate the in vivo and in vitro expression of FABP5 and FABP7 in oligodendrocyte lineage cells in the cortex and corpus callosum of adult mice, mixed cortical culture and oligosphere culture by immunofluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 51 publications
6
20
1
Order By: Relevance
“…We first examined localization of FABP7 in the mouse mPFC. Consistent with our former findings (Owada et al, ; Sharifi et al, ), FABP7 was localized in GFAP + astrocytes (Supp. Info.…”
Section: Resultssupporting
confidence: 93%
“…We first examined localization of FABP7 in the mouse mPFC. Consistent with our former findings (Owada et al, ; Sharifi et al, ), FABP7 was localized in GFAP + astrocytes (Supp. Info.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, the proportion of OPCs differentiating into MBP + /OLIG2 + myelin‐sheath forming oligodendrocytes is also significantly reduced (WT: 27% MBP + /OLIG2 + cells, Fabp7 KD: 5% MBP + /OLIG2 + cells, p = .03, unpaired Student's t ‐test) (Figure d,g). These findings concur with a study by Sharifi and colleagues, whose data was also consistent with a role for FABP7 in OPC differentiation (Sharifi et al, ). In the same publication it was also shown that the knockout of Fabp7 ( Fabp7 KO) affected the OPC proliferation capacity in vitro (Sharifi et al, ).…”
Section: Resultssupporting
confidence: 93%
“…There are ten FA binding proteins (FABPs), of which FABP3, FABP5, and FABP7 are expressed in the CNS (Owada, Yoshimoto, & Kondo, ). FABP7 is mainly expressed in astrocytes (Owada et al, ) and oligodendrocyte progenitor cells (OPCs; Sharifi et al, ), a progenitor cell giving rise to mature oligodendrocytes (OLs) in development and in response to injury (Franklin & ffrench‐Constant, ). OPCs isolated from Fabp7 knockout ( Fabp7 KO) mice have impaired differentiation in vitro (Sharifi et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, a seperate factor active at the right-hand site of the astrocyte cluster (figure 2C) suggests that there exists an intermediate checkpoint between the astrocytes and OPCs. This factor is characterized by the highly variable Fabp7 , a regulator of both astrocytes as well as OPCs (14, 15). Further effect of the cell cycle can be observed in the small set of protruding cells in the OPC 2 cluster as it is no longer present in the last embedding.…”
Section: Resultsmentioning
confidence: 99%